Exploring Reading Identity: Urban Parents Defining Themselves As Readers - Catherine Compton-Lilly (Networks: An Online Journal for Teacher Research, 2000)
As part of a teacher-research study I interviewed ten of my urban first grade students and their parents about reading. One parent, Ms. Webster, referred to people who read a lot as "bookworms" and "bookish people" who "don't have no fun." She explained, "All they do is sit in the house and read books all day long or sit outside and read books. . .